ITASE Impulse Radar Hercules Dome to South Pole ... - Christianson, Knut; Hoffman, Andrew; Jacobel, Robert; Welch, Brian (U.S. Antarctic Program (USAP) Data Center, 2023)
This dataset contains high-frequency impulse radar data collected by the United States portion of the International TransAntarctic Scientific Expedition (ITASE) 2001-2002 traverse from the vicinity of Hercules Dome, Antarctica to the South Pole. ...